Osteological study of morphometric analysis of acromion process and its implication in impingement syndrome - Hamzah Muzammil Hafezji (National Journal of Clinical Anatomy, 2021)
Introduction: Acromial morphology along with its position (slope/tilt) has a role in shoulder impingement. Acromioplasty is an important step in rotator cuff repair. Thus, knowledge of morphometric variations of the acromion is necessary. The aim of the study was to determine acromion morphometry and to correlate the morphometry of acromion with the dimensions of the scapula. Materials and Methods: The study was performed on 150 dried adult human scapulae, for which age and sex were not known. The shape of the acromion was observed from posterior and lateral view and different dimensions were measured. Results: The acromial curvature (as per Bigliani classification) was found to be flat (Category I) in 23.33%, curved (Category II) in 49.33%, and hooked (Category III) in 27.34% of scapulae. The acromial shape (from posterior view) was found to be quadrangular in 22%, triangular in 31.33%, and tubular in 46.67% of scapulae. The mean values of length, breadth, and thickness of acromion were 41.14 mm, 24.89 mm, and 6.95 mm, respectively. The acromion thickness was <8 mm in 87.33% and >8 mm in 12.67%. The mean of acromion slope and tilt were 28.23° and 42.47°, respectively. Conclusions: From the study, it may be concluded that a small proportion of the population (12.67%) may be prone to develop impingement due to more acromial thickness (>8 mm). The acromion slope and tilt are larger in our population which suggests lesser predisposition to impingement syndrome.